Implementation of Mail Server Based Of Squirrelmail Using Virtualization Technology at Universitas Muhammadiyah Sumatera Utara - Fanny Ramadhani; Rangga Mahara Miko; Nurul Sasti Diningsih; Muhammad Habib (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2021)
Server virtualization technology is the use of one physical machine by several server operating systems. The design and implementation of this mail server was built using Debian.5 as the base operating system server. The design and implementation of mail servers is built using the dns server, web server and mail server / squirrelmail, configured using the help of the virtualbox application as a server. DNS (Domain Name System) is a system that stores information about host names and domain names in the form of scattered databases (distributed databases) on a computer network, for example the Internet. The application used to handle the delivery of mail messages is the mail server. This mail server always receives messages from e-mail clients that the user uses, or maybe from other e-mail servers. Web mail functions to send and view e-mail messages through a web browser. The squirrelmail configuration is done by running the conf.pl: / var / www / wemail / config / conf.pl script. Exchange Server services include: Directory Service, Simple Mail Transfer Protocol (SMTP), Post Office Protocol (POP3), IMAP (Internet Message Access Protocol), Complementary Services, System Attendants. For Mail Server Delivery Process can be seen in number5.2.